2014
DOI: 10.5739/jfpsij.8.10
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Sliding-Part Temperature and Clearance Shape of A Slipper in Swashplate Axial Piston Motors

Abstract: Temperature and behavior of a piston motor slipper were examined using a test rig. The experimental setup comprised a tester, a hydraulic circuit, control units, and measuring instruments. The tester included a servomotor and a chamber enclosing two piston assemblies with slippers, a rotating disk, displacement sensors, and thermocouples. The sliding surface diameter of the test slipper was 32 mm; the test oil was hydraulic oil with VG46. Tests were conducted at supply pressures up to 35 MPa, rotational speeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A validation case is chosen from the published paper to verify the current result of the TEHD model of the slipper pair. A TEHD analysis of the slipper pair is presented in Kazama et al In this experiment, the eddy current sensors (eddy NCDT 3300) were found to be the smallest available on the market which are used to measure film thickness. The outer diameter of the displacement sensor is 2 mm.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A validation case is chosen from the published paper to verify the current result of the TEHD model of the slipper pair. A TEHD analysis of the slipper pair is presented in Kazama et al In this experiment, the eddy current sensors (eddy NCDT 3300) were found to be the smallest available on the market which are used to measure film thickness. The outer diameter of the displacement sensor is 2 mm.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 10 shows the film thickness calculated by HD, EHD, and TEHD and gives a comparison with the experimental result from Kazama. 31 As the slipper runs in the discharge stroke, the increase in the TEHD deformation is reflected immediately by a decrease in the fluid film thickness. The value of the film thickness under the TEHD lubrication condition is lower than those of the HD and EHD results.…”
Section: Comparison With Published Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the Slipper motion on the swashplate is dynamic, and taking into account the deformation caused by thermal expansion and hydrostatic pressure loads, the oil film thickness between the Slipper and Swashplate is not uniform at under the Slipper land. When the oil temperature is lowered, the increase in temperature becomes more pronounced [36]. The oil thickness between the Slipper land's size subjected to the greatest load and the swashplate is minimal (see illustration in FIGURE 15).…”
Section: The Effect Of Heat Exchange On Fluidmentioning
confidence: 99%
“…Chao et al [3] presented a review of the test rigs of the slipper bearing in axial piston pump. The test rigs are classified into four groups in this paper: stationary cylinder and swash plate [22], stationary cylinder and rotational swash plate without tilt [23,24], stationary cylinder and rotational swash plate with tilt [25] and stationary swash plate and rotational cylinder [26,27].…”
Section: Introductionmentioning
confidence: 99%